Use of nanoprobes to identify iron-silicates in a glass/iron/argillite system in deep geological disposal. (September 2019) - Carrière, C.; Dillmann, P.; Foy, E.; Neff, D.; Dynes, J.J.; Linard, Y.; Michau, N.; Martin, C.
Highlights: A glass/iron/claystone system was altered at 50 °C for 4.5 years in Andra's underground research laboratory in Bure, France. Creation of a new database of reference spectra obtained on iron-silicate end-members by STXM at Si K-edge. Multi-scale (macro-micro-nano) and multitechnical (SEM-EDX, μRaman, STXM and TEM) characterization to identify iron-silicate. Nanometric crystallized Fe(III)-rich smectites were detected in the glass alteration layer and in the iron corrosion products. Abstract: The understanding of glass alteration mechanisms in contact with iron is a major issue to study the long-term behavior of radioactive waste package in repository conditions. A glass/iron/claystone system was altered in contact with COx water at 50 °C for 4.5 years in Andra's underground research laboratory in Bure, France. Multiscale and multitechnical (SEM-EDX, μRaman, STXM and TEM) characterization of the system revealed the presence of nanometric crystalline Fe(III)-rich smectite, assimilated to nontronite, in the glass alteration layer and in corrosion products. These phyllosilicates were identified by STXM using a comparative approach with a database of reference spectra obtained on iron-silicate.